2022
DOI: 10.1051/0004-6361/202142147
|View full text |Cite
|
Sign up to set email alerts
|

Solis

Abstract: Context. Isotopic fractionation is an important tool for investigating the chemical history of our Solar System. In particular, the isotopic fraction of nitrogen (14N/15N) is lower in comets and other pristine Solar System bodies with respect to the value measured for the protosolar nebula, suggesting a local chemical enrichment of 15N during the formation of the Solar System. Therefore, interferometric studies of nitrogen fractionation in Solar System precursors are needed for us to obtain clues about our ast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Roueff et al 2015;Wirström & Charnley 2018;Loison et al 2019;Hily-Blant et al 2020). However, recent observational works have highlighted the importance of isotope-selective photodissociation of N 2 in explaining the local variation in the 14 N/ 15 N ratios in massive molecular clouds, low-mass Class 0/I objects, IRDCs, and protoplanetary discs (Colzi et al 2019;Bergner et al 2020;Fontani et al 2020Fontani et al , 2021Hily-Blant et al 2019;Evans et al 2022;Spezzano et al 2022), as suggested by chemical models (e.g. Furuya & Aikawa 2018;Visser et al 2018;Lee et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Roueff et al 2015;Wirström & Charnley 2018;Loison et al 2019;Hily-Blant et al 2020). However, recent observational works have highlighted the importance of isotope-selective photodissociation of N 2 in explaining the local variation in the 14 N/ 15 N ratios in massive molecular clouds, low-mass Class 0/I objects, IRDCs, and protoplanetary discs (Colzi et al 2019;Bergner et al 2020;Fontani et al 2020Fontani et al , 2021Hily-Blant et al 2019;Evans et al 2022;Spezzano et al 2022), as suggested by chemical models (e.g. Furuya & Aikawa 2018;Visser et al 2018;Lee et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The FIR 4 region (L = 1000 L e ; Crimier et al 2009) is known to be the most bright and centrally concentrated dust condensation within the embedded protocluster (Chini et al 1997;Lis et al 1998;Johnstone & Bally 1999). Previous millimeter and submillimeter interferometric observations have suggested possible star formation activity within the FIR 4 region (Shimajiri et al 2008;Takahashi et al 2008;López-Sepulcre et al 2013;Fontani et al 2017;Osorio et al 2017;Favre et al 2018;Nakamura et al 2019;Tobin et al 2019;Evans et al 2022). Multiwavelength infrared and centimeter observations have also revealed that the region contains several sources, indicating the presence of protostellar candidates (Reipurth et al 1999;Megeath et al 2012;Furlan et al 2016;Osorio et al 2017).…”
Section: Discussionmentioning
confidence: 97%
“…López-Sepulcre et al (2013) proposed that the FIR 4 region could be a H II region powered by a B3-B4 type young star. The third scenario is that the FIR 4 region is irradiated by an external source but not by flow-3 (Fontani et al 2017;Favre et al 2018;Evans et al 2022). These three scenarios have been mainly examined with regard to (sub)millimeter interferometric observations with a single pointing.…”
Section: Star Formation Environment In the Fir 4 Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, OMC-2 FIR 4 was thoroughly studied with different telescopes and at different wavelengths (e.g. Takahashi et al 2008;Kama et al 2013Kama et al , 2015Furlan et al 2014;López-Sepulcre et al 2017;Evans et al 2022). Its envelope size and luminosity were estimated to be ∼10 4 au and ≤1000 L ⊙ (Crimier et al 2009;Furlan et al 2014).…”
Section: Introductionmentioning
confidence: 99%